Factors that influence general practitioners' choice of hospital when referring patients for elective surgery. - Mahon, A (1993)
To describe the factors that influence general practitioners' choice of hospital when referring patients for elective surgery in three specialties, a postal questionnaire was distributed in January 1991 to 449 doctors who had referred patients to one of six hospitals in the North Western Regional Health Authority. Responses were received from 260 general practitioners (58%). Of the respondents 95% selected 'local and convenient' as a factor that commonly influenced their choice of hospital for at least one specialty and 65% mentioned this across all three specialties. Seventy four per cent mentioned patient preference as influencing choice for at least one specialty and 57% across all three specialties. Only 32% of doctors mentioned waiting times for appointment across the three specialties and 26% waiting times for surgery across the three specialties. When asked to select the single most important factor 'local and convenient' was selected by 33% of general practitioners for a least one specialty, the general standard of clinical care by 28% and waiting time for appointment by 23%. Patient preference was only selected by 6% of doctors as the most important factor. It is of note that 33% of general practitioners perceived there to be no choice of hospital for at least one specialty and 14% thought this to be the single most important influence on choice for at least one specialty. Approximately half the general practitioners (49%) considered it always or often appropriate to give their patients a choice. Most general practitioners received waiting time information from hospitals in their own health district but fewer received such information from hospitals outside their district.(ABSTRACT TRUNCATED AT 250 WORDS)